The Influence of Food Chain Puzzle Learning Media on Learning Outcomes in Class V Science Subjects at State Elementary School 024767 Binjai - Febrian Dolinta Ginting; Fahrur Rozi; Wildansyah Lubis; Imelda Free Unita Manurung; Lidia Simanihuruk (Formosa Journal of Multidisciplinary Research, 2023)
Learning media functions as a tool to convey subject matter in a learning context. The aim of this research is to assess the impact of using learning media in the form of the Food Chain Puzzle on learning outcomes in science subjects, especially in Theme 5 Sub Theme 2 Learning 1 in class V of SD Negeri 024767 Binjai for the 2023/2024 academic year. This research is a quantitative type of research and uses an experimental method with a quasi-experimental design. The research results show that the T-test value for the experimental posttest is 0.000, and the control posttest value is also 0.000. Because these values ​​are less than or equal to 0.05, it can be concluded that the use of learning media in the form of the Food Chain Puzzle has a significant influence on learning outcomes in science subjects, especially in Theme 5 Sub Theme 2 Learning 1 in class V of State Elementary Schools. 024767 Binjai for the 2023/2024 academic year.